Sandwich-cultured hepatocytes: utility for in vitro exploration of hepatobiliary drug disposition and drug-induced hepatotoxicity. (May 2013) - De Bruyn, Tom; Chatterjee, Sagnik; Fattah, Sarinj; Keemink, Janneke; Nicolaï, Johan; Augustijns, Patrick; Annaert, Pieter
<x xml:space="preserve">Abstract</x> Introduction: The sandwich-cultured hepatocyte (SCH) model has become an invaluable in vitro tool for studying hepatic drug transport, metabolism, biliary excretion and toxicity. The relevant expression of many hepatocyte-specific functions together with the in vivo-like morphology favor SCHs over other preclinical models for evaluating hepatobiliary drug disposition and drug-induced hepatotoxicity. Areas covered: In this review, the authors highlight recommended procedures required for reproducibly culturing hepatocytes in sandwich configuration. It also provides an overview of the SCH model characteristics as a function of culture time. Lastly, the article presents a summary of the most prominent applications of the SCH model, including hepatic drug clearance prediction, drug–drug interaction potential and drug-induced hepatotoxicity. Expert opinion: When human (cryopreserved) hepatocytes are used to establish sandwich cultures, the model appears particularly valuable to quantitatively investigate clinically relevant mechanisms related to in vivo hepatobiliary drug disposition and hepatotoxicity. Nonetheless, the SCH model would largely benefit from better insight into the fundamental cell signaling mechanisms that are critical for long-term in vitro maintenance of the hepatocytic phenotype. Studies systematically exploring improved cell culture conditions (e.g., co-cultures or extracellular matrix modifications), as well as in vitro work identifying key transcription factors involved in hepatocyte differentiation are currently emerging.